2004
DOI: 10.1021/jp046314g
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved FTIR Spectroscopy of the Photointermediates Involved in Fast Transient H+ Release by Proteorhodopsin

Abstract: Proteorhodopsin (pR) is a homologue of bacteriorhodopsin (bR) that has been recently discovered in oceanic bacterioplankton. Like bR, pR functions as a light-driven proton pump. As previously characterized by laser flash induced absorption spectroscopy (Krebs, R. A.; Alexiev, U.; Partha, R.; DeVita, A. M.; Braiman, M. S. BMC Physiol. 2002, 2, 5), the pR photocycle shows evidence of light-induced H(+) release on the 10-50 micros time scale, and of substantial accumulation of the M intermediate, only at pH value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…1). The green-absorbing PR is activated at alkaline pH in either a phospholipid or detergent environment, 13,16,17 which corresponds well with the pH of the ocean near the surface (~8.0). Photoexcitation of PR results in the translocation of a proton across the membrane.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…1). The green-absorbing PR is activated at alkaline pH in either a phospholipid or detergent environment, 13,16,17 which corresponds well with the pH of the ocean near the surface (~8.0). Photoexcitation of PR results in the translocation of a proton across the membrane.…”
Section: Introductionmentioning
confidence: 71%
“…The proteorhodopsin photocycle when the protein is suspended in a (A) phospholipid bilayer, 14,16,19 or (B) detergent suspension. 9,11 Lifetimes are shown for select photostates that have been resolved in the cited references.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, measurements by Krebs et al (53) at pH 9.5 in diheptanoylphosphatidylcholine micelles resulted in a proton signal of reversed polarity: proton release first (20 Ws), followed by proton uptake (0.3 s) somewhat earlier than the decay of the slow component of M and completion of the photocycle (0.6 s) occur (53). Subsequent FTIR study suggested that the release cannot be from Asp97 since it remained protonated in this time domain (54). A study of the pH dependence of proton release and uptake with a pH sensitive SnO 2 electrode by Tamogami et al confirmed these two different kinds of signals (55), at neutral and high pH.…”
Section: Discussionmentioning
confidence: 99%
“…A similar band in the BR photocycle was assigned to a Glu side chain acting as proton donor. In analogy the corresponding band in PR is tentatively assigned to a partial deprotonation or a disturbance of Glu108, although this is still under discussion (18). This band is a marker for the L‐intermediate at low pH.…”
mentioning
confidence: 99%